2017
DOI: 10.1016/j.nbd.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immune-modifying nanoparticles as a therapy for spinal cord injury in mice

Abstract: Intravenously infused synthetic 500 nm nanoparticles composed of poly(lactide-co-glycolide) are taken up by blood-borne inflammatory monocytes via a macrophage scavenger receptor (macrophage receptor with collagenous structure), and the monocytes no longer traffic to sites of inflammation. Intravenous administration of the nanoparticles after experimental spinal cord injury in mice safely and selectively limited infiltration of hematogenous monocytes into the injury site. The nanoparticles did not bind to resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 69 publications
(107 reference statements)
3
63
0
Order By: Relevance
“…As previously described, slides were washed in PBS‐Triton (PBS‐T) (Triton concentration is given thusly) (0.05% Triton X‐100) and incubated with primary antibodies at 4°C overnight in blocking media (5% normal donkey serum in PBS‐T). Primary antibodies used were: GFAP (Dako, Carpinteria, CA, Z0334, 1:1,000; Abcam, Cambridge, MA, ab4674, 1:1,000) and MARCO (BAF2956, 1:50) . For GFAP, primary antibodies were visualized with Alexa 647 (far red), 594 (red), and 488 (green) Alexa Fluor conjugated secondary antibodies at 1:1,000 dilution (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously described, slides were washed in PBS‐Triton (PBS‐T) (Triton concentration is given thusly) (0.05% Triton X‐100) and incubated with primary antibodies at 4°C overnight in blocking media (5% normal donkey serum in PBS‐T). Primary antibodies used were: GFAP (Dako, Carpinteria, CA, Z0334, 1:1,000; Abcam, Cambridge, MA, ab4674, 1:1,000) and MARCO (BAF2956, 1:50) . For GFAP, primary antibodies were visualized with Alexa 647 (far red), 594 (red), and 488 (green) Alexa Fluor conjugated secondary antibodies at 1:1,000 dilution (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, mice were anesthetized with 50mg/kg pentobarbital followed by cardiac perfusion with 30mL of phosphate-buffered saline (PBS). 13 For CCI, injured section of brain (3mm 3 lesional/perilesional area) was microdissected at 72 hours after injury. For CHI experiments, whole brain tissue was processed at 72 hours after injury as well.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…While the precise mechanism for tolerance is not fully understand, this study and others using PLGA NPs displaying self‐antigens have demonstrated both size and charge play a role in efficacy; NPs ≈500 nm in diameter with negative surface charges display the highest level of colocalization with MARCO and efficacy in promoting tolerance. Recent studies, which are discussed in Section , have also demonstrated that negatively charged particles delivered without self‐antigens can drive tolerance …”
Section: Nps and Mps Offer Attractive Features As Carriers Of Signalsmentioning
confidence: 98%
“…As described in Section , recent studies have demonstrated that biomaterials display intrinsic properties that can drive inflammatory or proimmune function in immune cells. Other recent studies have described tolerogenic properties of various biomaterials, including synthetic polymers such as PLGA and PS, QDs, gold NPs, and cellulose nanofibers . These intrinsic biomaterial properties are now starting to be explored in therapeutic contexts as tools to promote tolerance in preclinical models of autoimmune disease.…”
Section: Biomaterials Display Intrinsic Immunogenic Materials Propertimentioning
confidence: 99%